Cadabra and Python algorithms in General Relativity and Cosmology II: Gravitational Waves - Castillo-Felisola, Oscar; Price, Dominic T; Scomparin, Mattia (arXiv.org, 2022)
Computer Algebra Systems (CASs) like Cadabra Software play a prominent role in a wide range of research activities in physics and related fields. We show how Cadabra language is easily implemented in the well established Python programming framework, gaining excellent flexibility and customization to address the issue of tensor perturbations in General Relativity. We obtain a performing algorithm to decompose tensorial quantities up to any perturbative order of the metric. The features of our code are tested by discussing some concrete computational issues in research activities related to first/higher-order gravitational waves.